Kaɨmakɨ guiye fɨnuafue: the preparation of the food of our people (2014)
This bilingual (Witoto-Spanish) text contains three parts. The first part deals with the labor activities involved in the preparation of a horticultural garden (chagra): slashing, burning, selection of seeds, planting, cultural labors, importance of the chagra for nourishing the body, and the construction of true men and women. The second part contains several autobiographical texts narrated from the perspective of food: Anastasia Candre’s entrance in the boarding school in La Chorrera (1969-1975), what they ate there and how people’s chagras were and the products they sold to the school; the “Time of the Mafia” (1980-1983), when, because of the coca-boom, Indians no longer made chagras and new food products arrived; Anastasia’s arrival to Leticia (1983-1985), the new products she saw, the Indians she met and the chagras they had; and Anastasia’s return to La Chorrera (2013), her visit to her sister’s chagra and her criticism to what she saw there. The third part contains the processes of preparation of dry cassava bread, wet cassava bread (arepa), wrapped manioc dough (tamales), thick manioc flour (fariña), thick cassava bread, chili sauce and manioc starch.